The 2P3A Learning Model in Developing Argumentation Ability, Literacy Skills and Problem Solving Skills - Nur Afni; Husnaini Bahri (BIOPENDIX, 2025)
Education is requires students to have skills to support the learning process in the 21st century. 21st century learning skills can be trained in various ways including through the learning model used by the teacher. The 2P3A learning model consists of 5 main stages, namely the Preparation stage, the Problem Statement stage, the Analyze stage, the Argument stage and the Application stage. This learning model focuses on training and improving argumentation skills, problem solving skills and literacy skills of students. Argumentation skills are enhanced at the Argument stage where students will be trained to state their views about a problem, Problem solving skills are improved through the Analyze stage where students are trained to look for and analyze problems given and Literacy Skills can be trained through the Preparation stage where students will be accustomed to read the learning material before starting the learning process.